2016
DOI: 10.1002/jssc.201600482
|View full text |Cite
|
Sign up to set email alerts
|

Poly(glycidyl methacrylate)‐grafted hydrophobic charge‐induction agarose resins with 5‐aminobenzimidazole as a functional ligand

Abstract: Hydrophobic charge-induction chromatography is a new technology for antibody purification. To improve antibody adsorption capacity of hydrophobic charge-induction resins, new poly(glycidyl methacrylate)-grafted hydrophobic charge-induction resins with 5-aminobenzimidazole as a functional ligand were prepared. Adsorption isotherms, kinetics, and dynamic binding behaviors of the poly(glycidyl methacrylate)-grafted resins prepared were investigated using human immunoglobulin G as a model protein, and the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Liu et al. modified the above mentioned preparation protocol further by grafting poly(glycidyl methacrylate) on agarose resin with subsequent coupling of 5‐aminobenzimidazole as a functional ligand . Adsorption isotherms, kinetics, and dynamic binding behavior of the resulting resins were investigated using human IgG as a model protein, and the effect of ligand density was evaluated.…”
Section: Polymeric Mixed‐mode Stationary Phasesmentioning
confidence: 99%
“…Liu et al. modified the above mentioned preparation protocol further by grafting poly(glycidyl methacrylate) on agarose resin with subsequent coupling of 5‐aminobenzimidazole as a functional ligand . Adsorption isotherms, kinetics, and dynamic binding behavior of the resulting resins were investigated using human IgG as a model protein, and the effect of ligand density was evaluated.…”
Section: Polymeric Mixed‐mode Stationary Phasesmentioning
confidence: 99%
“…Cation exchanger SP Sepharose FF showed high capacity but poor selectivity and salt tolerance, and fermentation broth needed to be diluted before adsorption [9]. Mixed‐mode chromatography is a novel technology for protein separation [10–12], and mixed‐mode resin CST‐II FF showed salt tolerance but low selectivity [13]. Capto MMC was used to separate rHSA from rice seeds extract, but the selectivity was also limited [14].…”
Section: Introductionmentioning
confidence: 99%
“…And compared to the nongrafted resins, the dextran-grafted layer on the resin could increase the ligand density, enhance the mass transport in the pore, and improve the dynamic adsorption at high kinetics. In the further research, Liu et al 12 have prepared new poly(glycidyl methacrylate)-grafted hydrophobic charge-induction resins with 5-aminobenzimidazole as the functional ligand. The results showed that the resins with the ligand density of 330 μmol/g (G-ABI-330 resin) had the maximum adsorption capacity and binding affinity for hIgG, which were better than the HCIC resins reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…And compared to the nongrafted resins, the dextran-grafted layer on the resin could increase the ligand density, enhance the mass transport in the pore, and improve the dynamic adsorption at high kinetics. In the further research, Liu et al have prepared new poly­(glycidyl methacrylate)-grafted hydrophobic charge-induction resins with 5-aminobenzimidazole as the functional ligand. The results showed that the resins with the ligand density of 330 μmol/g (G-ABI-330 resin) had the maximum adsorption capacity and binding affinity for hIgG, which were better than the HCIC resins reported in the literature. , Moreover, the dynamic binding capacity value at 10% breakthrough of the G-ABI-330 resins could reach to 76.3 mg/g at linear velocity 300 cm/h, which was also higher than those of nongrafted resins and other polymer-grafted HCIC resin (G-MMI and MMI-B-XL-200). , It is obvious that suitable polymers grafted to the resins could improve the binding ability between chromatographic resins and antibody.…”
Section: Introductionmentioning
confidence: 99%